ANALISIS DAMPAK ZAKAT PRODUKTIF TERHADAP KESEJAHTERAAN MUSTAHIK DENGAN PENDEKATAN CIBEST - Ach Yasin; Santi Ariyani (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2022)
Productive zakat is one of distribution of aid that has two dimensions, the economic and spiritual dimensions. The effectivity of productive zakat economically and spiritually can be measured through the calculation of the CIBEST index (Center for Islamic Business and Economic Studies). This study aims to analyze the impact of zakat on the mustahiq’ household income, mustahiq’s spiritual and household conditions with Quadrant CIBEST before and after receiving zakat assistance from empowerment and utilization programs Laznas Inisiatif Zakat Indonesia East Java Representative. The study used a descriptive quantitative research method with 11 mustahiq households as the respondents. The instrument used was the Center for Islamic Business and Economic Studies (CIBEST). The study results showed that the distribution of productive zakat funds could improve the welfare of the mustahiq households by 9% and minimize material poverty by 9%.